Sweets for the foe – effects of nonstructural carbohydrates on the susceptibility of Quercus robur against Phytophthora quercina. Issue 4 (6th June 2014) - Angay, Oguzhan; Fleischmann, Frank; Recht, Sabine; Herrmann, Sylvie; Matyssek, Rainer; Oßwald, Wolfgang; Buscot, François; Grams, Thorsten E. E.
Summary The root‐rot pathogen Phytophthora quercina is a key determinant of oak decline in Europe. The susceptibility of pedunculate oak (Quercus robur) to this pathogen has been hypothesized to depend on the carbon availability in roots as an essential resource for defense. Microcuttings of Q. robur undergo an alternating rhythm of root and shoot growth. Inoculation of mycorrhizal (Piloderma croceum) and nonmycorrhizal oak roots with P. quercina was performed during both growth phases, that is, root flush (RF) and shoot flush (SF). Photosynthetic and morphological responses as well as concentrations of nonstructural carbohydrates (NSC) were analyzed. Infection success was quantified by the presence of pathogen DNA in roots. Concentrations of NSC in roots depended on the alternating root/shoot growth rhythm, being high and low during RF and SF, respectively. Infection success was high during RF and low during SF, resulting in a significantly positive correlation between pathogen DNA and NSC concentration in roots, contrary to the hypothesis. The alternating growth of roots and shoots plays a crucial role for the susceptibility of lateral roots to the pathogen. NSC availability in oak roots has to be considered as a benchmark for susceptibility rather than resistance against P. quercina.